1995
DOI: 10.1021/np50126a004
|View full text |Cite
|
Sign up to set email alerts
|

L-735,334, a Novel Sesquiterpenoid Potassium Channel-Agonist from Trichoderma virens

Abstract: A novel oleic acid ester of the carotane sesquiterpene 14-hydroxy CAF-603 was isolated from Trichoderma virens grown in a solid brown rice-based medium, a solid millet-based medium, or a mannitol-based liquid medium. Its structure was determined on the basis of ms and nmr analysis. It retains distinct biological activity on the high conductance calcium-activated potassium channel, unlike its analogues 14-hydroxy CAF-603, CAF-603 3-oleate, or CAF-603 3-linoleate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…Terpenoids such as dehydrosoyasaponin I (McManus et al, 1993), maxikdiol (Singh et al, 1994), and L-735,334 (Lee et al, 1995) have been identified as BK channel openers by use of 125 I-ChTX binding assay. Despite the structural dissimilarity, these three terpenoids share biological profiles; they can displace 125 I-ChTX, but not fully, and activate BK channel only when applied intracellularly in electrophysiological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Terpenoids such as dehydrosoyasaponin I (McManus et al, 1993), maxikdiol (Singh et al, 1994), and L-735,334 (Lee et al, 1995) have been identified as BK channel openers by use of 125 I-ChTX binding assay. Despite the structural dissimilarity, these three terpenoids share biological profiles; they can displace 125 I-ChTX, but not fully, and activate BK channel only when applied intracellularly in electrophysiological experiments.…”
Section: Discussionmentioning
confidence: 99%
“…3) exhibiting antifungal activity against various yeast and dermatophytes and having a remarkable effect on Candida albicans (Watanabe et al 1990). Lee et al (1995a) isolated an oleic ester derivative of 8 named L-735,334 (9) (Fig. 3), from T. virens grown in several culture broths.…”
Section: Daucanesmentioning
confidence: 99%
“…3), from T. virens grown in several culture broths. Both metabolites, 8 and 9, are modulators of the high conductance calcium-activated potassium channel (Ondeyka et al 1995;Lee et al 1995a). Four new metabolites with carotane skeletons, trichocaranes A-D (10-13) (Fig.…”
Section: Daucanesmentioning
confidence: 99%
“…By using [McManus et al, 1993], maxikdiol [Singh et al, 1994], and L-735,334 [Lee et al, 1995b]. While DHS-1 was considerably more potent than maxikdiol and L-735,334 in binding and functional assays, they all opened the BK channels only when applied at the intracellular side of the membrane.…”
Section: Introductionmentioning
confidence: 99%